Sosialisasi Kesetaraan Gender Untuk Pencegahan Kekerasan Terhadap Perempuan di Dusun Ngrenak Kidul - Antonius Ian Bayu Setiawan (UNIB Press, 2024)
Gender issues are closely related to preventing violence against women. Women are often considered as weak creatures and very vulnerable to being targets of various forms of violence. Violence against women is currently a global problem that affects the mental, physical, and emotional well-being of women throughout the world. Providing outreach regarding gender equality to prevent violence and provide a better understanding of the target audience for teenagers. The aim of this activity is to increase teenagers' knowledge about sexual violence, reproductive health, and the concept of gender equality. The results of this activity show that teenagers in Ngrenak Kidul Hamlet understand the prevention of sexual violence and gender equality but have not fully implemented some of the actions that have been socialized.